A novel supercapacitor electrolyte of spiro-(1, 1')-bipyrolidinium tetrafluoroborate in acetonitrile/dibutyl carbonate mixed solvents for ultra-low temperature applications. (10th May 2016) - Cheng, Fang; Yu, Xuewen; Wang, Jing; Shi, Zhiqiang; Wu, Changcheng
Graphical abstract: Highlights: Ultra-low temperature electrolytes were demonstrated with 10 F cylindrical capacitor. Mixing DBC effectively enlarged low temperature operation range from −40 to −60 °C. The novel electrolytes showed excellent electrochemical performance at −60 °C. Abstract: A novel electrolyte of electric double-layer capacitors (EDLCs) for ultra-low temperature applications based on spiro-(1, 1')-bipyrolidinium tetrafluoroborate (SBP-BF4 ) dissolved in acetonitrile (AN) and AN + dibutyl carbonate (DBC) mixtures has been developed. The physic-chemical properties and electrochemical characterizations at low temperature have been demonstrated on pure AN and AN/DBC mixed electrolytes. From 20 to −50 °C, AN electrolyte shows a slight superiority of the capacitance, but the novel DBC-mixed electrolytes exhibit much higher ion conductivity and better electrochemical performance at −60 °C, while AN electrolyte does not cycle at all due to the crystallization of AN and precipitation of SBP-BF4 . The specific discharge capacitance of DBC mixtures maintain 92 F g −1 even at a high current density of 5 A g −1 . At −60 °C, from electrochemical impedance spectroscopy measurement, the whole resistance for AN electrolyte rapidly increased about 60 times higher than that of 20 °C, while those for DBC mixtures remain relatively low within the whole temperature range. The cycle performance test indicates the DBC mixtures exhibit extremely stable capacitance, especially at ultra-low temperature. The capacitance for DBC-20% electrolyte is 95 F g −1 even after 10000 cycles, which maintained 83% of the capacity of 20 °C.